The Crucial Role of PPARγ-Egr-1-Pro-Inflammatory Mediators Axis in IgG Immune Complex-Induced Acute Lung Injury - Yan, Chunguang; Chen, Jing; Ding, Yue; Zhou, Zetian; Li, Bingyu; Deng, Chunmin; Yuan, Dong; Zhang, Qi; Wang, Ximo (Frontiers in Immunology, 2021)
The ligand-activated transcription factor peroxisome proliferator-activated receptor (PPAR) γ plays crucial roles in diverse biological processes including cellular metabolism, differentiation, development, and immune response. However, during IgG immune complex (IgG-IC)-induced acute lung inflammation, its expression and function in the pulmonary tissue remains unknown. Objectives: The study is designed to determine the effect of PPARγ on IgG-IC-triggered acute lung inflammation, and the underlying mechanisms, which might provide theoretical basis for therapy of acute lung inflammation. Setting: Department of Pathogenic Biology and Immunology, Medical School of Southeast University Subjects: Mice with down-regulated or up-regulated PPARγ activity, and mice with down-regulation of Early growth response protein 1 (Egr-1) expression, and the corresponding controls. Interventions: Acute lung inflammation is induced in the mice by airway deposition of IgG-IC. Activation of PPARγ is achieved by using its agonist Rosiglitazone. PPARγ activity is suppressed by application of its antagonist GW9662 or shRNA. Egr-1 expression is down-regulated by using the gene specific shRNA. Measures and Main Results: We find that PPARγ expression at both RNA and protein levels is repressed during IgG-IC-induced acute lung inflammation, which is consistent with the results obtained from macrophages treated with IgG-IC. Furthermore, both in vivo and in vitro data show that PPARγ activation reduces IgG-IC-mediated pro-inflammatory mediators’ production, thereby alleviating lung injury. In terms of mechanism, we observe that the generation of Egr-1 elicited by IgG-IC is inhibited by PPARγ. As an important transcription factor, Egr-1 transcription is substantially increased by IgG-IC in both in vivo and in vitro studies, leading to augmented protein expression, thus amplifying IgG-IC-triggered expressions of inflammatory factors via association with their promoters. Conclusion: During IgG-IC-stimulated acute lung inflammation, PPARγ activation can relieve the inflammatory response by suppressing the expression of its downstream target Egr-1 that directly binds to the promoter regions of several inflammation-associated genes. Therefore, regulation of PPARγ-Egr-1-pro-inflammatory mediators axis by PPARγ agonist Rosiglitazone may represent a novel strategy for blockade of acute lung injury.